Analisis Prakiraan Jumlah Produksi Mie Menggunakan Metode Fuzzy Mamdani pada Pabrik Mie Lie - Ziyad, Ziyad Rofi Syamil; Astri, Astri Ismanto; Helga, Helga Alfrida Sephira; Farhan, Farhan Lintang Wicaksono; Bagus, Bagus Farhat Brori; Suhendi, Suhendi Irawan (Universitas Boyolali, 2024)
Mie Lie Factory is one of the MSMEs in producing semi-finished products with the products produced being egg noodles, wonton skins, and dimsum skins. Mie Lie Factory is experiencing a problem in its production due to the uncertainty of the amount of demand each month. Production planning and demand forecasting need to be done in order to overcome this problem. This study aims to determine the quantity of production based on demand forecasting and the amount of availability at Mie Lie Factory. Demand forecasting can be known from the company's historical data over the last 12 months using the time series method. The method used for production planning is the Mamdani fuzzy method. The results of this study are that the company can find the number of products for production activities in the next period. The amount of product demand in October 2024 is 498.5 kg with the amount of product inventory in September 2024 of 200 kg, so the amount of noodle production through the use of the Mamdani fuzzy method is 405 kg. This research is expected to help Mie Lie Factory in planning production every month.